STUDI HUBUNGAN ANTARA TIGA PARAMETER DENGAN MENGGUNAKAN MODEL GREENSHIELD, GREENBERG, UNDERWOOD DAN BELL PADA RUAS JALAN DR. SUDJONO KOTA MATARAM - ROHANI, ROHANI; HASYIM, HASYIM; SALSABILAH, PUTRI (Ganec Swara, 2025)
Dr. Sudjono Road is a National Road in Mataram City which is included in the collector road class, which connects various activity centers, such as educational activities, offices, economy and others. This causes the traffic flow to increase, which has an impact on traffic speed and density. This study aims to analyze the relationship between three parameters, namely volume (Q), speed (V) and density (D) of traffic according to existing conditions and find out the model that best suits the road. In analyzing the mathematical relationship between the three main variables of traffic flow, the Greenshield, Greenberg, Underwood and Bell models were used. The results show that the most suitable model is the Greenshield model compared to the other three models. So from the Greenshield model, the relationship between volume (Q), speed (V) and density (D) is obtained for the Jalan Dr. Sudjono from the East direction obtained: (Vs-D): Vs= 47.263 - 0.613× D, (Q-D): Q= 47.263 ×D-0.613×D^2, (Q-Vs): Q= 77.074×Vs–1.631×Vs2 and from the West direction obtained: (Vs-D): Vs= 56.398 - 0.846×D, (Q-D): Q=56.398 ×D-0.846×D2, (Q-Vs): Q= 66.627×Vs-1.181×Vs2. Based on a model that is suitable for Jalan Dr. Sudjono, namely the Greenshield model, the traffic flow characteristics from the East are obtained: (Qm) = 910,694 pcu/hour, maximum speed (Vm)=23,632 km/h, maximum density (Dm) = 93,624 pcu/km, free flow speed (Vsff) = 47,263 km/h and density during traffic jams (Dj) = 77,074 pcu/km and from the west it is obtained: (Qm)= 939,403 pcu/hour, (Vm) = 28,199 km/hour, (Dm) = 33,313 pcu/km, (Vsff) = 56,398 km/hour and (Dj) = 66,627 pcu/km.